Ovarian cancer modulates the immunosuppressive function of CD11b+Gr1+ myeloid cells via glutamine metabolism - Mary P. Udumula; Sharif Sakr; Sajad Dar; Ayesha B. Alvero; Rouba Ali-Fehmi; Eman Abdulfatah; Jing Li; Jun Jiang; Amy Tang; Thomas Buekers; Robert Morris; Adnan Munkarah; et al. (Elsevier, 2021)
Objective: Immature CD11b + Gr1+ myeloid cells that acquire immunosuppressive capability, also known as myeloid-derived suppressor cells (MDSCs), are a heterogeneous population of cells that regulate immune responses. Our study's objective was to elucidate the role of ovarian cancer microenvironment in regulating the immunosuppressive function of CD11b+Gr1+ myeloid cells. Methods: All studies were performed using the intraperitoneal ID8 syngeneic epithelial ovarian cancer mouse model. Myeloid cell depletion and immunotherapy were carried out using anti-Gr1 mAb, gemcitabine treatments, and/or anti-PD1 mAb. The treatment effect was assessed by a survival curve, in situ luciferase-guided imaging, and histopathologic evaluation. Adoptive transfer assays were carried out between congenic CD45.2 and CD45.1 mice. Immune surface and intracellular markers were assessed by flow cytometry. ELISA, western blot, and RT-PCR techniques were employed to assess the protein and RNA expression of various markers. Bone marrow-derived myeloid cells were used for ex-vivo studies. Results: The depletion of Gr1+ immunosuppressive myeloid cells alone and in combination with anti-PD1 immunotherapy inhibited ovarian cancer growth. In addition to the adoptive transfer studies, these findings validate the role of immunosuppressive CD11b+Gr1+ myeloid cells in promoting ovarian cancer. Mechanistic investigations showed that ID8 tumor cells and their microenvironments produced recruitment and regulatory factors for immunosuppressive CD11b+Gr1+ myeloid cells. CD11b+Gr1+ myeloid cells primed by ID8 tumors showed increased immunosuppressive marker expression and acquired an energetic metabolic phenotype promoted primarily by increased oxidative phosphorylation fueled by glutamine. Inhibiting the glutamine metabolic pathway reduced the increased oxidative phosphorylation and decreased immunosuppressive markers' expression and function. Dihydrolipoamide succinyl transferase (DLST), a subunit of α-KGDC in the TCA cycle, was found to be the most significantly elevated gene in tumor-primed myeloid cells. The inhibition of DLST reduced oxidative phosphorylation, immunosuppressive marker expression and function in myeloid cells. Conclusion: Our study shows that the ovarian cancer microenvironment can regulate the metabolism and function of immunosuppressive CD11b + Gr1+ myeloid cells and modulate its immune microenvironment. Targeting glutamine metabolism via DLST in immunosuppressive myeloid cells decreased their activity, leading to a reduction in the immunosuppressive tumor microenvironment. Thus, targeting glutamine metabolism has the potential to enhance the success of immunotherapy in ovarian cancer.